Implementation of p16/Ki67 dual stain cytology in a Danish routine screening laboratory: Importance of adequate training and experience. (7th September 2020) - Hammer, Anne; Gustafson, Line W.; Christensen, Pia N.; Brøndum, Rikke; Andersen, Berit; Andersen, Rikke H.; Tranberg, Mette
Abstract: Background: Immunocytochemical staining with p16/Ki67 has been suggested as a promising triage biomarker in cervical cancer screening. As dual staining is a subjective method, proper training may be required to ensure safe implementation in routine laboratories and reduce risk of misclassification. We determined concordance between novice evaluators and an expert, stratified by number of slides reviewed at three reading points. Methods: The study was conducted at the Department of Pathology, Randers, Denmark. Women were eligible if they were aged ≥45, had been enrolled in one of two ongoing clinical studies, and had a dual stain slide available. Dual staining was performed using the CINtec plus assay. Slides were randomly selected from three reading points at which novice evaluators had reviewed <30, ~300, and ≥500 dual stain slides respectively. Level of concordance was estimated using Cohen's Kappa, κ . Results: Of 600 eligible slides, 50 slides were selected for review as recommended by the manufacturer. Median age was 68 years (range: 58‐74). Overall concordance was good ( κ  = 0.68, 95% confidence interval [CI]: 0.60‐0.76), with an overall agreement of 84% (95% CI: 70.9%‐92.8%). Concordance improved with increasing number of slides reviewed at a given reading point, from a moderate concordance ( κ  = 0.47, 95% CI: 0.05‐0.90) after reviewing <30 slides to a good concordance ( κ  = 0.66, 95% CI: 0.20‐0.88) and a very good concordance ( κ  = 0.88, 95% CI: 0.66‐1.00) after reviewing ~300 and ≥500 slides, respectively. Conclusions: When interpreting dual stain slides from older women, concordance increased slightly as novice evaluators received more training and experience. Although further evaluation is warranted, these findings indicate that a significant amount of training and experience of novice evaluators may be needed to ensure accurate dual stain interpretation in this age group. Future studies should accurately describe training and experience of evaluators to enable a better comparison of concordance and diagnostic accuracy across studies. Trial registration: NCT04114968 and NCT04298957. Abstract : As training and experience in p16/Ki67 dual stain interpretation may affect concordance and possibly diagnostic accuracy of cervical precancer, it is important that future studies accurately describe any training and previous experience among evaluators to allow for a meaningful comparison of dual stain accuracy across studies. Furthermore, setting up proper dual stain training programs in routine screening laboratories is advisable to ensure sufficient interpretation skills among novice evaluators.